IMPROVING STUDENTS’ VOCABULARY THROUGH WORDWALL APPLICATION - Weran, Yohana; Nova; Lailatus Sa’adah (Pedagogic Research-Applied Literacy Journal, 2024)
This article used the library research method to gather information by understanding and researching theories from various sources such as books, journals, and existing studies. The method used qualitative research that focuses on gathering information about the natural environment and using researchers as the main instrument. This study aims to analyze the responses and experiences of first-year high school students and how the Wordwall application helps them improve their English vocabulary during their studies. Literary research method is used. The data collection method used is the documentation method. Content analysis was used as a data analysis technique. In order to maintain the accuracy of the evaluation and avoid false information, the material was analyzed by cross-checking and re-reading the literature, and the evaluator's comments were taken into account. The result of this study is that Wordwall proves to be an effective teaching method that helps improve students' vocabulary in preparation for future assignments. Word wall apps can also be used while studying, which is very useful for developing students' vocabulary